Analisis Laporan Keuangan Komersial dan Laporan Keuangan Fiskal Terhadap Pajak Badan Pada CV Setia Kawan Abadi - Ratna Putri, Fariska; Basri, Hasan; Sianturi, Murdan (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
The author aims to whether the variables of commercial financial statements and fiscal financial statements against corporate tax on CV Setia Kawan Abadi. This type of research uses positivistic data collection methods (concrete data), research data in the form of numbers that will be measured using financial statements. Data analysis methods Quantitative Analysis and descriptive analysis. As one of the potential state revenues, taxes are a top priority that can dominate state revenues. Every corporate taxpayer is obliged to prepare financial reports regularly and follow the applicable bookkeeping principles, namely financial reports based on Financial Accounting Standards known as commercial financial reports. However, the company also reports financial statements for taxes with reference to tax regulations. From the existing data, CV Setia Kawan Abadi experienced a profit for the 2019 period of Rp. 2,496,923,702 and for the 2020 period of Rp. 3,227,524,195, but this data is only based on existing financial reports without reconciliation. Reconciliation of Accounting and Tax Regulations can be explained by the difference in commercial profit and loss and fiscal profit and loss corrected positively in 2019, namely Income Tax Article 21 of Rp. 40,000,000, Employee Recreation of Rp. 26,000,000, Delivery Expenses of Rp. 141,049,272, Telephone Expenses of Rp. 75,388,404, a contribution of Rp. 5,560,000, dividends of Rp. 45,000,000 and for 2020, namely Income Tax Article 21 of Rp. 100,000,000, Employee Recreation of Rp. 23,000,000, Delivery Expenses of Rp.27,253,000, Telephone Expenses of Rp. 17,986,425, a contribution of Rp. 2,400,000, Dividend of Rp. 15,000,000. After the commercial financial statements are corrected, the fiscal financial statements. Then it can be known as Taxable Income. Taxable income in 2019 is delayed in September-December subject to a fine of Rp. 629,240 and in 2020 there is a delay in the same month subject to a fine of Rp. 684,400 and corporate income tax payable in 2019 profit before tax of Rp. 6,000,0000 after being multiplied by 25% by Rp.1,500,000 then calculating the tax payable for 2020 profit before tax is Rp.7,000,000 after being multiplied by 25% by Rp.1,750,000